Transcriptomes Divergence of Ricotia lunaria Between the Two Micro-Climatic Divergent Slopes at “Evolution Canyon” I, Israel - Qian, Chaoju; Yan, Xia; Yin, Hengxia; Fan, Xingke; Yin, Xiaoyue; Sun, Peipei; Li, Zhijun; Nevo, Eviatar; Ma, Xiao-Fei (Frontiers in Genetics, 2018)
As one of the hotspot regions for sympatric speciation studies, Evolution Canyon (EC) became an ideal place for its high level of micro-climatic divergence between interslopes. In this study, to shed light on the genetic mechanisms of sympatric speciation, phenotypic variation on flowering time and transcriptomic divergence were investigated between two ecotypes of Ricotia lunaria, which habitated on the opposite slopes of EC I (Lower Nahal Oren, Mt. Carmel, Israel) with only 100 meters apart from each other. Growth chamber results showed that flowering time of the ecotype from south-facing slope (SFS3) was significantly promoted with three months ahead to the one that from north-facing slope (NFS5). At the same floral development stage, transcriptome analysis showed that 1,064 unigenes were differentially expressed between the two ecotypes, which enriched in the four main pathways involved into abiotic and/or biotic stresses responses, as flavonoid biosynthesis, α-linolenic acid metabolism, plant-pathogen interaction and linoleic acid metabolism. Furthermore, based on Ka/Ks analysis, nine genes were detected to be involved into the ecological divergence between the two ecotypes, whose homologs functioned as RNA editing, ABA signaling, photoprotective response, chloroplasts protein-conducting channel and carbohydrate metabolic in Arabidopsis thaliana. Among them, four genes namely as SPDS1, FCLY, Tic 21 and BGLU25, also showed adaptive divergence between R. lunaria and A. thaliana, suggesting that these genes could play an important role in plant speciation, at least in Brassicaceae. Based on results of both the phenotype of flowering time and comparative transcriptome, we speculate that, after long time local adaptation to their micro-climatic environments between the opposite slopes, the molecular functions of these nine genes could have been diverged between the two ecotypes. They might differentially regulate the expression of the downstream genes and pathways that involved into the abiotic stresses, which could further differentiate the flowering time between the two ecotypes, and finally induce the reproductive isolation establishment by limiting their gene flow from each other.